Effects of laser surface remelting on the molten salt corrosion resistance of yttria-stabilized zirconia coatings. Issue 18 (15th December 2018) - Yi, Peng; Mostaghimi, Javad; Pershin, Larry; Xu, Pengyun; Zhan, Xianghua; Jia, Delong; Yi, Hao; Liu, Yancong
Abstract: In the present study, atmospheric plasma-sprayed yttria-stabilized zirconia coatings were post-remelted by a continuous diode laser to improve the hot corrosion resistance for as-sprayed coatings. The coating surfaces were covered with a salt mixture (V2 O5 and Na2 SO4 ) and then subjected to a hot corrosion test at 1100 °C in air. The influence of laser parameters including power and scanning rate on the coating microstructure and corrosion resistance was investigated. Results showed that the hot corrosion resistance can be improved by producing a dense and smooth surface and reducing the coating permeability to the molten salt. The transformation of the hot corrosion mechanisms was clarified on the basis of the observed corrosion behaviors. A laser power of 1500 W and scanning rate of 9 mm/s can produce minimal surface roughness with few segmented cracks, which can provide improved performance of the hot corrosion resistance.